PUBLICATION OF THE WEEK. (Bookseller, 2002)
Lists several books published in the year 2002. 'Betelvine Cultivation and Management of Diseases,' by J.P. Chaurasia; 'Caribbean Elegance,' by Michael Connors; 'More Space,' by Fay Sweet; 'Backward Mosaics,' by Connie Sheerin; 'Brice Marden: His Own Choice,' by Brice Marden; 'History of Film,' by Jack C. Ellis.